Import of proteins into yeast mitochondria: the nuclear MAS2 gene encodes a component of the processing protease that is homologous to the MAS1-encoded subunit. - Jensen, R E (1988)
The mas2 mutant of Saccharomyces cerevisiae is temperature sensitive for import of proteins into mitochondria. To identify the lesion in this mutant, we have cloned and sequenced the wild-type MAS2 gene and determined the intracellular location of its protein product. MAS2 encodes an essential 53-kd protein that is located in the mitochondrial matrix and is homologous to the MAS1 protein, a previously identified subunit of the protease that cleaves presequences from mitochondrial precursor proteins. The activity of this enzyme is temperature sensitive in mas2 cells. Together with the results of the accompanying study these results show that MAS2 and MAS1 encode the two subunits of the processing protease.